Varieties of religious nationalism - Koenig, Matthias; Knöbl, Wolfgang (Religion and national identities in an enlarged Europe, 2015)
The aim of this book has been to analyze changing relationships between religion and national identity in an enlarging European Union. How did the horizontal and vertical European integration that dramatically sped up after 1990 affect understandings of nationhood? More specifically, how did the creation and eastern enlargement of the European Union alter the ways in which religion enters into codes of collective identity? Was the process of European integration yet another stage in an ongoing process of secularization, as some might have expected or hoped? Or did integration prompt more complex reconfigurations of religion and national identities?